On two new species of Cypricercus Sars, 1895 (Crustacea, Ostracoda) from Brazil with a discussion on the taxonomy of the genus - de Almeida, Nadiny Martins; Ferreira, Vitor Góis; Higuti, Janet; Martens, Koen (Zootaxa, 2021)
We describe two new species of Cypricercus, Cypricercus alfredo sp. nov. and Cypricercus tiao sp. nov., and briefly redescribe the female of Cypricercus centrurus (Klie, 1940) from Brazilian floodplains. Both new species have the elongated carapace which is characteristic of the genus. Cypricercus alfredo sp. nov. was found as both sexual and asexual populations and has a posterior spine on the right valve and differs from the Brazilian C. centrurus by the position and the size of spine and the size and shape of the carapace. Cypricercus tiao sp. nov. was found as one asexual population only and lacks a posterior spine on the right valve. Cypricercus populations in Brazil mostly consist exclusively of asexual females, but some sexual populations and populations with mixed reproduction can also be found. This genus occurs primarily in the Southern Hemisphere, but some species can also be found in the southern part of North America and in India. We also present a re-appraisal of all species presently allocated to the genus, primarily based on original descriptions.